STUDY OF CYLPEBS CHILLING - E. I. Marukovich; A. M. Branovicky; Y. A. Lebedinsky; Y. V. Sachenko; V. A. Harkov; O. G. Prohocky (Литьë и металлургия)
Methods of increasing the shock resistance of cast-iron grinding bodies are researched. The models of heat transfer in the process of casting and shock-abrasive wear are presented. Tooling to produce experimental samples of milling bodies chilling(gravity die casting) is manufactured, samples of cylpebs are produced.